Single and 14-day repeated dose inhalation toxicity studies of hexabromocyclododecane in rats. (May 2016) - Song, Naining; Li, Lei; Li, Haishan; Ai, Wenchao; Xie, Wenping; Yu, Wenlian; Liu, Wei; Wang, Cheng; Shen, Guolin; Zhou, Lili; Wei, Changlei; Li, Dong; et al.
Abstract: Limited toxicological information is available for hexabromocyclododecane (HBCD), a widely used additive brominated flame retardant. Inhalation is a major route of human exposure to HBCD. The aim of this study was to determine the acute inhalation toxicity and potential subchronic inhalation toxicity of HBCD in Sprague-Dawley rats exposed to HBCD only through inhalation. The acute inhalation toxicity of HBCD was determined using the limit test method on five male and five female Sprague-Dawley rats at a HBCD concentration of 5000 mg/m 3 . Repeated-dose toxicity tests were also performed, with 20 males and 20 females randomly assigned to four experimental groups (five rats of each sex in each group). There were three treatment groups (exposed to HBCD concentrations of 125, 500, and 2000 mg/m 3 ) and a blank control group (exposed to fresh air). In the acute inhalation toxicity study, no significant clinical signs were observed either immediately after exposure or during the recovery period. Gross pathology examination revealed no evidence of organ-specific toxicity in any rat. The inhalation LC50(4 h) for HBCD was higher than 5312 ± 278 mg/m3 for both males and females. In the repeated dose inhalation study, daily head/nose-only exposure to HBCD at 132 ± 8.8, 545.8 ± 35.3, and 2166.0 ± 235.9 mg/m 3 for 14 days caused no adverse effects. No treatment-related clinical signs were observed at any of the test doses. The NOAEL for 14-day repeated dose inhalation toxicity study of HBCD is 2000 mg/m 3 . Highlights: This study determined the acute and potential subchronic toxicities of HBCD in S.D. rats through head/nose-only exposure. The inhalation LC50(4 h) for HBCD was higher than 5312 ± 278 mg/m 3 for both males and females. In the repeated dose inhalation study, the NOAEL for 14-day repeated dose inhalation toxicity study of HBCD was 2000 mg/m 3 .